2021
DOI: 10.1016/j.jsps.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Student-Led discharge counseling program for High-Risk medications in a teaching hospital in Saudi Arabia: A pilot study

Abstract: Discharge counseling by pharmacists reduces adverse medication events, emergency department visits, and readmissions. Studies indicate that pharmacy students in advanced pharmacy practice experiences (APPE) can deliver effective medication-related activities. An open label randomized controlled trial was conducted in adults discharged on warfarin, insulin, or both. Pharmacy students performed medication reconciliation, structured medication counseling, and follow-up calls 72-hours post-discharge. The usual car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“… NA High Salmany S (Salmany et al, 2018 ) 2017 Jordan March – May 2015, 30-days N = 332 I:166 C: 166 I: 47.2 (16) C: 49.2 (16) I: 46.4% C:48.2% Oncology patients who were discharged from inpatient services on weekdays (Sunday through Thursday) Healthcare utilisation, (n (percentage)) of patients: ED visits: I: 63 (44%) vs. C: 80 (52%), P = 0.123 Hospital readmission: 57 (37%) vs. C: 66 (43%), P = 0.317 Neutral Some concerns Karaoui L (Karaoui et al, 2021 ) 2021 Lebanon August 2017 – July 2019, 30-days N = 200 I:100 C:100 I: 74.7 (12.09) C: 73.2 (14.74) I: 46% C: 43% Age ≥18 years, discharged on oral anticoagulant for a therapeutic indication, able to communicate in Arabic or English Healthcare utilisation (primary outcome): All-cause readmission rates including unplanned physician’s clinic visit, (n (percentage)) of patients: I: 15 (15%) vs. C: 12 (12%), OR¶: 0.847 (95% CI 0.380–1.886), P = 0.802 Readmission related to anticoagulant use (n (percentage)) of patients: I: 7% vs. C: 7%, OR 0.684 (95% CI 0.193–2.419), P = 0.650 Neutral High Marzoog H (Marzoog et al, 2021 ) 2021 Iraq August 2018 – April 2019, 12-weeks N = 50 I: 25 C: 25 I: 57 (14.6) C: 61.9 (9.6) I: 56% C: 64% Patients admitted with acute heart failure Healthcare utilisation: hospital readmission for acute heart failure (n (percentage)) of patients I: 6 (24%) vs C: 15 (60%), P = Not calculated. NA High Bawazeer G (Bawazeer et al, 2021 ) 2021 Kingdom of Saudi Arabia (KSA) October 2016 – April 2017, 30-days N = 98 I = 56 C: 51 ...…”
Section: Resultsmentioning
confidence: 99%
“… NA High Salmany S (Salmany et al, 2018 ) 2017 Jordan March – May 2015, 30-days N = 332 I:166 C: 166 I: 47.2 (16) C: 49.2 (16) I: 46.4% C:48.2% Oncology patients who were discharged from inpatient services on weekdays (Sunday through Thursday) Healthcare utilisation, (n (percentage)) of patients: ED visits: I: 63 (44%) vs. C: 80 (52%), P = 0.123 Hospital readmission: 57 (37%) vs. C: 66 (43%), P = 0.317 Neutral Some concerns Karaoui L (Karaoui et al, 2021 ) 2021 Lebanon August 2017 – July 2019, 30-days N = 200 I:100 C:100 I: 74.7 (12.09) C: 73.2 (14.74) I: 46% C: 43% Age ≥18 years, discharged on oral anticoagulant for a therapeutic indication, able to communicate in Arabic or English Healthcare utilisation (primary outcome): All-cause readmission rates including unplanned physician’s clinic visit, (n (percentage)) of patients: I: 15 (15%) vs. C: 12 (12%), OR¶: 0.847 (95% CI 0.380–1.886), P = 0.802 Readmission related to anticoagulant use (n (percentage)) of patients: I: 7% vs. C: 7%, OR 0.684 (95% CI 0.193–2.419), P = 0.650 Neutral High Marzoog H (Marzoog et al, 2021 ) 2021 Iraq August 2018 – April 2019, 12-weeks N = 50 I: 25 C: 25 I: 57 (14.6) C: 61.9 (9.6) I: 56% C: 64% Patients admitted with acute heart failure Healthcare utilisation: hospital readmission for acute heart failure (n (percentage)) of patients I: 6 (24%) vs C: 15 (60%), P = Not calculated. NA High Bawazeer G (Bawazeer et al, 2021 ) 2021 Kingdom of Saudi Arabia (KSA) October 2016 – April 2017, 30-days N = 98 I = 56 C: 51 ...…”
Section: Resultsmentioning
confidence: 99%
“…Following title and abstract screening, 274 full texts were retrieved. A total of 126 RCTs involving 97 408 participants met our inclusion criteria (Figure 2). The study characteristics are presented in eAppendix 3 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…Pooling data from the 73 studies (85 direct comparisons) involving 77 201 participants, low-complexity (OR, 0.78; 95% CI, 0.66 to 0.92) and medium-complexity (OR, 0.82; 95% CI, 0.68 to 0.97) interventions were associated with decreased odds of readmission at 30 days compared with usual care (Figure 3; eAppendix 2 in Supplement 1). High-intensity interventions were not associated with reductions in readmissions (OR, 0.96; 95% CI, 0.80 to 1.15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saudi Arabia, the inaccurate medication reconciliation process across all levels of care is fairly common due to the lack of clear implementation methods, human resources, and limited Saudi literature on the issue ( Mazhar et al, 2017 ). While there have been several attempts to assess the role of pharmacists in the medication reconciliation process during TOC ( Mazhar et al, 2017 , Elamin et al, 2021 , Aljumah, 2013 ), the involvement of pharmacy interns has been given less attention ( Bawazeer et al, 2021 ). Only a few studies have evaluated the effect of pharmacy interns on TOC activities which have shown that interns can be effective in conducting this service, in addition to enhancing their confidence and clinical skills ( Walker et al, 2010 , McLaughlin et al, 2015 , Champion et al, 2019 , Andrus and Stevenson, 2015 , Hertig et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%